THE EFFECT OF RISK AND QUALITY PERCEPTIONS OF COSMETIC SAMPLES ON SAM PLE USE AND PURCHASE CONVERSION - In-Seon Shim; Kyung-Ja Kim (Adisam Publisher, 2025)
Aims: The purpose of this study is to investigate the impact of risk and quality perceptions on cosmetic sample use and purchase conversion rate among Korean adult women. Methods: An online survey was conducted among 433 Korean adult women in their 20s to 50s. The survey collected data on the consumers' risk perception, quality perception, sample usage rate, and actual purchase conversion rate about cosmetic samples. Results: The results indicate that risk perception of cosmetic samples has a negative effect on quality perception and sample usage rate. However, quality perception has a positive effect on sample usage rate and actual purchase conversion rate. Furthermore, the study found that the sample usage rate has a positive effect on actual purchase conversion rate. Conclusions: Future research could expand the scope to include other demographic groups or cultural contexts. Cosmetic companies can use these findings to design more effective free sample promotions that address customers' risk perceptions while enhancing their quality perceptions. This study may contribute to improving customer satisfaction and loyalty in the cosmetics industry by providing insights into how cosmetic companies can effectively use free samples as a sales promotion tool.